Evaluation of The Association Between Depression and Diabetes Among The Diabetic Patients Treated in Benghazi Diabetic Clinic - S. Baiu, Heithum; A. Al-Maghriby, Sarah; A. Al-Houty, Malak; M. Al-Farjany , Sarah; M. Bala, Duaa; Y. Al-Sultany , Maryam (Libyan Journal of Public Health Practices, 2026)
Diabetes and depression have a bidirectional relationship and are prevalent among Libyans. Thus, in this concurrent case-control study, the relationship between depression and diabetes was investigated. The data were collected simultaneously from a total of 112 participants (56 diabetics and 56 controls). The data were collected through a written questionnaire. The binary logistic regression was used to evaluate the relationship between socio-demographic variables, lifestyle variables, depression and diabetes. Marriage was statistically significantly related to diabetes compared to single individuals (P= 0.014; odd ratio= 49.742, 95% CI (2.193 1128.483)). The confidence interval range is very wide. It is an imprecision due to the small sample size. BMI was statistically significantly related to diabetes (P = 0.013; odd ratio = 1.136, 95% CI (1.027 to 1.257)). Eye diseases were statistically significantly related to diabetes compared to “the ‘no complications’ group”. (P= 0.001; odd ratio= 18.196, 95% CI (3.312 to 99.972)). However, the confidence interval is very wide. It is an imprecision due to the small sample size. However, the other variables were not statistically significantly related to diabetes. The research hypothesis was not supported since there is no sufficient evidence for the relationship between depression and diabetes. It is recommended for health educators to encourage diabetic patients, patients with depression, and people without diabetes and depression to follow a healthy lifestyle and to adhere to the depression screening test (diabetic patients and the public).